HUBUNGAN JENIS KELAMIN DENGAN KEBIASAAN MEROKOK, CUCI TANGAN DAN PERILAKU GIZI DI MASA PANDEMI COVID 19 - emy yuliantini; miratul haya; andi eka yunianto; sherly sherly; tri antini (Poltekkes Kemenkes Semarang, 2021)
Background: Coronavirus 2019 (COVID-19) is a respiratory disease caused by corona virus. Smokers are the most vulnerable group form Covid-1. Dirty hands can spread disease by providing entry to pathogens, bacteria, or viruses. Handwashing could be effective and efficient prevention to prevent covid-19 infection.Objective: To determine the relationship between gender and smoking habits, handwashing and nutritional behavior among respondents.Methods: A descriptive-analytic study with a cross-sectional design. Respondents were 966 people who lived in Bengkulu Province. Data collection was carried out by online questionnaire which were distributed through WhatsApp media. Data analysis used the chi-square test.Results: There were significant relationship between gender and smoking habits (p = 0.003), gender and handwashing (p = 0.000), gender and nutritional behavior related with fresh food consumptions (p = 0.026). There were no relationship between gender and nutritional behavior related to preserved/instant foods consumption (p = 0.463), nutritional behavior and fruit-vegetable consumption habits (p = 0.090).Conclusion: There is a relationship between gender and smoking and handwashing habits.